PEMBANGUNAN APLIKASI PENGUMPUL BERITA DARI MEDIA DARING MENGGUNAKAN WEB FRAMEWORK CODEIGNITER DAN FLASK - Satriajati, Salim; Santoso, Ibnu (Jurnal Sistem Informasi, 2021)
Advances in information and communication technology today cause access to news to be faster. Gathering news from online media is important to support various interests. News collection also needs to be done automatically to be efficient and effective. So, in this research, a news collector application will be built to get some news from online news site. The application is built using two web frameworks, namely Codeigniter and Flask. In addition, the Python-based Scrapy package is also used as a tool for web crawling and web scraping. Black-box testing is used to evaluate system functionality. Based on the results of black-box testing, it can be concluded that all functions of the news collector application from online news site that have been created can run as expected by the researcher.